Access To Finance, Financial Literacy, And Business Planning On SME Growth - Indra Wijaya (Malaqbi Publisher, 2026)
Small and Medium Enterprises (SMEs) play a vital role in economic development; however, their growth is often constrained by financial and managerial challenges. This study aims to examine the effect of access to finance, financial literacy, and business planning on SME growth. A quantitative research approach was employed using a cross-sectional survey design, with data collected from SME owners and managers through structured questionnaires. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results indicate that access to finance, financial literacy, and business planning all have a positive and significant effect on SME growth. Among these variables, financial literacy was found to have the strongest influence, followed by business planning and access to finance. These findings suggest that while financial resources are essential for business expansion, the ability to manage finances effectively and implement strategic planning plays a more critical role in driving sustainable growth. The study highlights the importance of integrating financial inclusion initiatives with financial education and business planning support to enhance SME performance. The findings provide valuable implications for policymakers, financial institutions, and SME practitioners in developing strategies to foster business growth in a dynamic and competitive environment.